Methyl isocyanate inhalation induces tissue factor-dependent activation of coagulation in rats. (4th May 2019) - Rancourt, Raymond C.; Rioux, Jacqueline S.; Veress, Livia A.; Garlick, Rhonda B.; Croutch, Claire R.; Peters, Eric; Sosna, William; White, Carl W.
Abstract: Methyl isocyanate (MIC) is a highly toxic industrial chemical causing acute lethality after inhalation. The objective of this study was to determine whether alterations in hemostasis also occur in the immediate hours after exposure. Male rats were exposed to MIC (125–500 ppm) by nose-only vapor inhalation for 30 min. Arterial O2 saturation was monitored prior to exposure, and hourly thereafter. Rats were euthanized at 1, 2, 4, and 8 hr and plasma analyzed for recalcification clotting time, tissue factor (TF) activity, and protein levels. Hypoxemia, as assessed by pulse oximetry, was an early feature of MIC inhalation. In contrast to sham or low (125 ppm) concentrations, 250 and 500 ppm MIC caused significant declines in blood oxygen saturation (% SpO2 ) at 1 hr, which remained at deficit during the postexposure period. Commensurate with hypoxemia, plasma clotting time was significantly accelerated 1 hr after MIC inhalation (sham treatment: 955 ± 62.8 s; 125 ppm MIC: 790 ± 62 s; 250 ppm: 676 ± 28.0 s; 500 ppm: 581 ± 175 s). This procoagulant effect was transient, with no difference observed between sham and all MIC groups by 8 hr. Similarly, elevated TF activity and protein were detected in plasma 1 hr after MIC inhalation, each of which showed a progressive decline back to control levels at later timepoints. This study demonstrates that MIC inhalation resulted in hypoxemia and transient hypercoagulability of blood. Accelerated clotting occurred rapidly and was likely due to intravascular TF, which initiates the extrinsic coagulation pathway.